Faktor-faktor yang Mempengaruhi Penerapan Higiene dan Sanitasi pada Penjual Makanan di Sekolah di Yogyakarta: Factors Influencing Hygiene and Sanitation Practices among School Food Vendors in Yogyakarta - Muhammad Hafizh Hariawan; Herwinda Kusuma Rahayu; Tendriana Ayu Winarsih; Asna Afifah Wahyuaji (Amerta Nutrition, 2025)
Background: Food safety in school environments is a key factor in supporting the continuity of educational activities. However, monitoring of hygiene and sanitation practices among school food vendors remains suboptimal. Unsafe or contaminated food can pose serious health risk to students. Poor hygiene and sanitation practices by food vendors are a key contributor to foodborne illnesses in schools. Objectives: This study aimed to evaluate the hygiene and sanitation practices of school food vendors in Yogyakarta and the factors influencing the implementation of these practices. Methods: A cross-sectional study employing a quantitative observational design was conducted in nine elementary schools in Sleman, involving 60 food vendors operating in the surrounding school areas. Associations between independent variables (age, gender, educational background, years of experience, training history, knowledge level, and attitude) and hygiene and sanitation practices were assessed using the chi-square test. Logistic regression analysis was performed to examine the model and identify factors influencing the implementation of hygiene and sanitation practices among school food vendors. Results: The study found that 55% of respondents did not adequately implement hygiene and sanitation practices, particularly in the area of personal hygiene. Slightly more than half of the food vendors (51.67%) had insufficient knowledge. Education level (AOR=1.58, 95% CI=1.05-3.616) and knowledge level (AOR=6.535, 95% CI=1.652-25.86) were significantly associated with the implementation of hygiene and sanitation practices. Conclusions: Education and knowledge levels are key factors influencing hygiene and sanitation practices among school food vendors. Targeted educational interventions for all stakeholders involved in program implementation are recommended to enhance knowledge and promote good hygiene and sanitation practices.